Adaptive K-Parallel Best-First Search: A Simple but Efficient Algorithm for Multi-Core Domain-Independent Planning - Vidal, Vincent; Bordeaux, Lucas; Hamadi, Youssef (Proceedings of the International Symposium on Combinatorial Search, 2010)
Motivated by the recent hardware evolution towards multi-core machines, we investigate parallel planning techniques in a shared-memory environment. We consider, more specifically, parallel versions of a best-first search algorithm that run K threads, each expanding the next best node from the open list. We show that the proposed technique has a number of advantages. First, it is (reasonably) simple: we show how the algorithm can be obtained from a sequential version mostly by adding parallel annotations. Second, we conduct an extensive empirical study that shows that this approach is quite effective. It is also dynamic in the sense that the number of nodes expanded in parallel is adapted during the search. Overall we show that the approach is promising for parallel domain-independent, suboptimal planning.